2002
DOI: 10.1098/rspb.2001.1914
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of offspring sex ratio by second-mated female house wrens

Abstract: In 1973, Trivers and Willard proposed that offspring sex ratio should be associated with the quality of parental care likely to be provided to the offspring. We tested this hypothesis by comparing fledgling sex ratios in nests of first- and second-mated female house wrens (Troglodytes aedon). In our Wyoming population, second-mated females typically receive little or no male parental assistance and fledge fewer and lower-quality young compared with first-mated females. Assuming that being of lower quality has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
1
15
2
Order By: Relevance
“…Thus, our data corroborate the results of previous studies on the yellow-headed blackbird Xanthocephalus xanthocephalus (Patterson et al 1980), oriental reed warbler Acrocephalus orientalis (Nishiumi et al 1996;Nishiumi 1998), house wren Troglodytes aedon (Albrecht & Johnson 2002) as well as earlier work on great reed warblers studied in Sweden (Westerdahl et al 2000) that proposed adaptive explanation for observed patterns of sex ratios. This difference may lie in differences in resources for nestling provisioning that are higher at primary than secondary nests, due to greater feeding assistance of males at primary nests and in different costs imposed by sons and daughters (Trivers & Willard 1973;Bensch & Hasselquist 1994;Westerdahl et al 2000).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, our data corroborate the results of previous studies on the yellow-headed blackbird Xanthocephalus xanthocephalus (Patterson et al 1980), oriental reed warbler Acrocephalus orientalis (Nishiumi et al 1996;Nishiumi 1998), house wren Troglodytes aedon (Albrecht & Johnson 2002) as well as earlier work on great reed warblers studied in Sweden (Westerdahl et al 2000) that proposed adaptive explanation for observed patterns of sex ratios. This difference may lie in differences in resources for nestling provisioning that are higher at primary than secondary nests, due to greater feeding assistance of males at primary nests and in different costs imposed by sons and daughters (Trivers & Willard 1973;Bensch & Hasselquist 1994;Westerdahl et al 2000).…”
Section: Discussionsupporting
confidence: 82%
“…The adaptive significance of this behaviour lies in differences in future reproductive value of nestlings of one sex relatively to nestlings of the other sex. In agreement with these expectations, many studies have shown that females may produce adjusted brood sex ratio as a response to their body condition, female mating status, timing of breeding and/or male attractiveness (see Hasselquist & Kempenaers 2002;Komdeur & Pen 2002 for previous reviews; Albrecht & Johnson 2002;Griggio et al 2002;Velando 2002;Gwinner & Schwabl 2005;Husby et al 2006, Freed et al 2009Du & Lu 2010;Philip et al 2010). However, some *Correspondence: Pavol Prokop, Department of Biology, University of Trnava, Priemyselná 4, SK-91843 Trnava, Slovakia.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Evidence supporting this hypothesis has been reported in several species of birds: studies have found a lower proportion of sons among the offspring of mothers with secondary-mate status in house wrens, great reed warblers, oriental reed warblers, and yellow-headed blackbirds (Albrecht et al, 2002;Westerdahl et al, 2000;Nishiumi, 1998;and Patterson et al, 1980; reviewed in Hasselquist & Kempenaers, 2002), and one study has found a lower proportion of sons among females who have changed mates, compared to females who remain with the same male (Oddie & Reim, 2002). In humans, there were many nineteenth century reports of a lower percentage of boys among human births occurring outside of marriage (Darwin, 1874), and studies in modern Kenya have found a lower percentage of sons among polygynously married women (Whiting, 1993;Dahl and Moretti, 2004).…”
Section: Introductionmentioning
confidence: 57%
“…This further raises the premium on the production of fit sons. Finally, results of several studies suggest that female house wrens have some control over the sex of their offspring (Albrecht 2000;Albrecht & Johnson 2002;Janota et al 2002;Dubois et al 2006; but see Johnson et al 2005).…”
Section: Introductionmentioning
confidence: 99%